Weight distribution and the risk of type 2 diabetes among middle- to high-income women in Saudi Arabia: A cross-sectional study. (August 2022) - Hakim, Noor
Abstract: Aims: Several studies from developed countries have found a lower prevalence of diabetes and obesity among higher socioeconomic groups; however, limited studies have evaluated the risk of diabetes and prevalence of obesity among middle- to high-income populations in developing countries. Therefore, this study explored the risk of developing type 2 diabetes mellitus (T2DM) and weight status of female students in private universities in Saudi Arabia. Methods: This cross-sectional study included 121 female students aged ≤25 years. Diabetes risk was evaluated using the Finnish Diabetes Risk Score. Weight was assessed by calculating the body mass index. Results: In total, 35.5% of students had a slightly elevated risk and 10.8% had a moderate to high risk of developing T2DM; one-third (29.7%) were overweight or obese. The risk of developing T2DM was low in most of the normal weight and underweight groups, moderate to high among 22.2% of the overweight participants, and high in over half of the participants with obesity (55.5%). Conclusions: large proportion of the study sample was slightly elevated to a high risk of developing T2DM, and nearly one-third of the study population had a BMI of ≥25 kg/m2. The elevated risk of T2DM among young female students is alarming and requires early identification of modifiable risk factors to minimize the risk of developing T2DM in later life. Highlights: Here, one-third of middle- to high-income female students were overweight or obese. The risk of developing diabetes increases with body weight status. The elevated risk of T2DM among young female is alarming and require more attention.